2015
DOI: 10.3109/15376516.2014.997947
|View full text |Cite
|
Sign up to set email alerts
|

Effects of curcumin and tannic acid on the aluminum- and lead-induced oxidative neurotoxicity and alterations in NMDA receptors

Abstract: Exposure to aluminum (Al) and lead (Pb) can cause brain damage. Also, Pb and Al exposure alters N-methyl-d-aspartate receptor (NMDAR) subunit expression. Polyphenols such as tannic acid and curcumin are very efficient chelator for metals. The effects of curcumin and tannic acid (polyphenols) on Al(3+)- and Pb(2+)-induced oxidative stress were examined by investigating lipid peroxidation (LPO) levels, antioxidant enzyme activities, acetyl cholinesterase (AChE) activity and also NMDA receptor subunits 2A and 2B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 49 publications
2
18
0
1
Order By: Relevance
“…Previous studies have reported that curcumin decreases AChE activity in rat brain [51][52][53]. In vitro experiments also confirmed that curcumin inhibits AChE activity and has an IC 50 value of 67 µmol/L [54].…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have reported that curcumin decreases AChE activity in rat brain [51][52][53]. In vitro experiments also confirmed that curcumin inhibits AChE activity and has an IC 50 value of 67 µmol/L [54].…”
Section: Discussionsupporting
confidence: 61%
“…Tu Baijie's study found that BaP and lead exert synergistic effects; BaP can enhance the neurotoxicity of lead (Tu et al, 2004). Both aluminum and lead are neurotoxic metals and are thought to be related to neurodegenerative dis-eases (Weidenhamer et al, 2014); their toxicity mechanisms are similar (Tüzmen et al, 2014). According to the present study, BaP may enhance the neurotoxicity of aluminum, which warrants further study.…”
Section: Discussionmentioning
confidence: 58%
“…increase of the concentrations of NR2A and NR2B subunits of N -methyl- d -aspartate receptors, elevation of the activities of antioxidant enzymes, decrease of lipid peroxidation in the brain hippocampus in Wistar rats after 16-weeks exposure of animals to Al 3+ and Pb 2+ (tannic acid at 50 mg/kg b.w./day; a nasogastric probe was used) [91];…”
Section: Figurementioning
confidence: 99%